Agricultural engineering education in Nigeria (2005)
Early agricultural engineering services required on Nigerian farms were provided by civil engineers and agronomists some of who later retrained to form the first crops of Nigerian agricultural engineers. Agricultural engineering training was substantially done overseas until about the early 1960s when local opportunities started to be available. Agricultural engineering education started with training in farm mechanization laying emphasis on tractorization in the colleges of agriculture and polytechnics, and later expanded to cover all aspects of agricultural engineering. Agricultural engineering education in Nigeria is offered by the universities, polytechnics and colleges of agriculture. Ownership and funding of tertiary institutions include the federal and state governments, private individuals and religious organizations. Quality assurance is achieved through setting of minimum academic standards and occasional programme accreditations by the Nigerian universities commission, the national board for technical education and the council for the regulation of engineering in Nigeria. Agricultural engineers are engaged in virtually all sectors of the economy. This paper discuses the historical development of agricultural engineering education in Nigeria highlighting the entry requirements, training and regulations, professional bodies and the sectors where the products are making their contributions towards the national development. It concludes by calling on all stake holders to understand and appreciate the role of the profession in national development and give it the desired support.